Wastewater Stabilisation Ponds System: Global Sensitivity Analysis on Network Design - M.P. Ochoa; V. Estrada; P. Hoch (Chemical engineering transactions, 2016)
In this work, a wastewater treatment network (WWTN) consisting of a system of ponds is modelled rigorously, taking into account dynamic mass balances for the main groups of bacteria, together with different types of organic load, algae biomass, nutrients, etc. To obtain the optimal configuration, we had first formulated a superstructure embedding these rigorous models as a mixed integer non-linear programming (MINLP) problem, with the objective to synthesise and design the WWTN that minimises the total annual costs, subject to environmental regulations. Then, a global sensitivity analysis (GSA) is performed on this kinetic dynamic model for the obtained optimal configuration of three stabilisation ponds (two aerobic ponds in series followed by a facultative one) to determine the most influential parameters of the model considering the whole range of parameters variation, as well as parameter ranking. GSA is implemented using Sobol’s method, a variance based technique. The technique is implemented within gPROMS platform, a differential algebraic equation oriented environment where stochastic simulations are performed. Temporal profiles for the first order, total order and interactional sensitivity indices are obtained for the main differential and algebraic state variables. Numerical results provide useful information about the complex relationships between technological, economic and environmental variables of the processes in the WWTN design optimisation.